The effect of disinfection protocols on dimensional accuracy of irreversible hydrocolloids and Candida albicans colonisation - Ahmad, Norfaezah; Ahmad Zawawi, Nur Dini; Muhammad, Nur Farah Athirah; Nasir, Siti Hajjar; Arzmi, Mohd Hafiz (IIUM Journal of Orofacial and Health Sciences, 2024)
Irreversible hydrocolloid is a widely used impression material in dental practices. However, improper disinfectant protocols may affect the dimensional accuracy of the cast and increase susceptibility towards cross-infection. This study investigated the effect of disinfectants and disinfection protocols on the dimensional accuracy of alginate impression and Candida albicans biofilm formation. For methodology, an alginate impression was developed using an acrylic maxillary edentulous master cast with 3 reference points. 60 3cm round alginate beads were synthesised and treated with 2% Aseptoprint, 1% sodium hypochlorite (NaOCl) or 3% MD 520 solutions for 2 min, 1 h, 6 h, and 24 h. For the antibiofilm assay, beads were inoculated with C. albicans (ATCC MYA 4901) for 24 h, and Colony-Forming Units (CFUs) were counted using a haemocytometer, then analysed via two-way Analysis of Variance (ANOVA). Dimensional accuracy was assessed by treating the developed alginate impressions in 2% Aseptoprint, 1% NaOCl, and 3% MD 520, respectively, for 2 min, 1 h, 6 h, and 24 h. Three linear measurements were obtained and compared against the master cast and analysed statistically using Friedman Tests. The results showed that a significant reduction of CFUs was recorded after disinfection with 3% MD 520 and 2% Aseptoprint (P < 0.05). Dimension of alginate impressions was significantly changed after 6 and 24 h of disinfection time. In conclusion, the use of 3% MD 520 and 2% Aseptoprint with 1 hour immersion time is recommended for effective alginate impression disinfection with minimal change in dimensional accuracy.